Pemberdayaan PKK Desa Pagarawan melalui Budi Daya Tanaman Sayuran dengan Sistem Hidroponik - Eries Dyah Mustikarini; Ratna Santi; Ismed Inonu (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
Hydroponic vegetable cultivation for PKK mothers aims to produce safe household-scale vegetables. This activity was an opportunity for the community to increase income. Community service activities were carried out in Pagarawan Village, Merawang Subdistrict, Bangka District in May–August 2018. The purpose of community service activities was to provide counseling and training on plant cultivation with a hydroponic system. Kind of vegetables that are cultivated are mustard greens. The hydroponic system that was socialized to participants was a floating and flowing hydroponic system using a wick. The results of a survey to training participants showed that 38.46 strongly agreed, 61.54 agreed, and 0 disagreed with hydroponic vegetable cultivation. The results of SWOT analysis showed that to increased community motivation in conducting hydroponic crop cultivation there needs a capital/investment, support from academics, and the government. The results of analysis of mustard greens farming in hydroponics require an initial capital of IDR 2,016,000, a profit of IDR 502,570/month, and venture capital can be returned within 4 months. The hydroponic plant system is very good to be developed because besides being able to meet the needs of vegetables for the household it can also increase family income.